Answer:
(6, - 3 )
Step-by-step explanation:
Given the 2 equations
3x + 5y = 3 → (1)
x + 2y = 0 → (2)
Rearrange (2) expressing x in terms of y by subtracting 2y from both sides
x = - 2y → (3)
Substitute x = - 2y into (1)
3(- 2y) + 5y = 3
- 6y + 5y = 3
- y = 3 ( multiply both sides by - 1 )
y = - 3
Substitute y = - 3 into (3) for corresponding value of x
x = - 2(- 3) = 6
Solution is (6, - 3 )
Given:
Required
Determine the domain
A relation is represented as:
Where:
are the domain of the relation
So, by comparison:
or represents the domain
the ordered pairs are
(5,5) & (-1,-3)